Membentuk Kebiasaan Sehat: Edukasi Gizi dan Kebersihan Gigi untuk Anak Pra Sekolah di Nagari Cingkaring - Dewi Rosmalia; Zulfikri; Zulni Fitri; Ayu Lukmawati; H.M Faisal (CV. CENDIKIA JENIUS INDONESIA, 2024)
Dental and gum health problems in pre-school children often arise duetoalackof understanding of the importance of a healthy diet and proper brushing habits. Thiscommunity service aims to provide education about the importance of ahealthydiet and proper brushing habits to pre school children in Nagari Cingkaring, Banuhampu District, and increase awareness of dental and gumhealth. Themethod of community service activities is through a series of educational sessionsabout healthy and destructive foods for dental health, providing foodsthat arehealthy and destructive for teeth, educating good and correct toothbrushing, demonstrating tooth brushing, providing toothbrush packages and carryingout tooth brushing together to practice proper tooth brushing habits. The resultsof thisactivity show the enthusiasm of children in the implementation of theprogram, increased knowledge of pre-school children about healthy and destructivefoodsfor dental health, and an increase in the habit of brushing teeth regularly. Inconclusion, this community service activity succeeded in raising the awarenessofpre-school children about the importance of a healthy diet and dental hygiene, with the hope that they can maintain these habits into adulthood, therebyreducingthe risk of dental and gum health problems in the future.